find the sum with explanation each
Attachments:
![](https://hi-static.z-dn.net/files/d31/13d3d17523de71dcdf1fa461c57b6ade.jpg)
Answers
Answered by
1
___Sum of pq + 3qr - rp and 2pq + qr - 3rp___
= pq + 3qr - rp + 2pq + qr - 3rp
= 3pq + 4qr - 4rp
___Subtraction of 3pq + 4qr - 4rp from 11pq - 6qr + 10rp___
= ( 11pq - 6qr + 10rp ) - ( 3pq + 4qr - 4rp )
= 11pq - 6qr + 10rp - 3pq - 4qr + 4rp
= 7pq - 8qr + 14rp
= pq + 3qr - rp + 2pq + qr - 3rp
= 3pq + 4qr - 4rp
___Subtraction of 3pq + 4qr - 4rp from 11pq - 6qr + 10rp___
= ( 11pq - 6qr + 10rp ) - ( 3pq + 4qr - 4rp )
= 11pq - 6qr + 10rp - 3pq - 4qr + 4rp
= 7pq - 8qr + 14rp
Similar questions